Imrobable cause : a novel of suspense - Jance, Judith A., 1944- (J.P. Beaumont ;, 1988)
Perhaps it was fitting justice: a dentist who enjoyed inflicting pain was murdered in his own chair.The question is not who wanted Dr. Frederick Nielsen dead, but rather who of the many finally reached the breaking point.The sordid details of this case, with its shocking revelations of violence, cruelty, and horrific sexual abuse, would be tough for any investigator to stomach.But for Seattle Homicide Detective J.P. Beaumont, the most damning piece of the murderous puzzle will shake him to his very core -- because what will be revealed to him is nothing less than the true meaning of unrepentant evil.